2023
DOI: 10.1021/acsami.2c23236
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Cyclability and Moisture Durability of NaCrO2 Sodium-Ion Battery Cathode via Simultaneous Al Doping and Cr2O3 Coating

Abstract: Although there are many cathode candidates for sodium-ion batteries (NIBs), NaCrO 2 remains one of the most attractive materials due to its reasonable level of capacity, nearly flat reversible voltages, and high thermal stability. However, the cyclic stability of NaCrO 2 needs to be further improved in order to compete with other state-of-the-art NIB cathodes. In this study, we show that Cr 2 O 3 -coated and Al-doped NaCrO 2 , which is synthesized through a simple one-pot synthesis, can achieve unprecedented c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Ikhe et al studied the aqueous stability of Al-doped NaCrO 2 . 82 In Fig. 11a, NaCrO 2 particles displayed a strong affinity for water leading to dispersion and suspension upon soaking.…”
Section: Ph and Chemical Titrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Ikhe et al studied the aqueous stability of Al-doped NaCrO 2 . 82 In Fig. 11a, NaCrO 2 particles displayed a strong affinity for water leading to dispersion and suspension upon soaking.…”
Section: Ph and Chemical Titrationmentioning
confidence: 99%
“…However, it is important to note that after reviewing various XPS analysis results in the literature, we have encountered instances of misinformation and conflicts arising from peak identification and fitting. 37,46,59,[77][78][79][80][81][82] To address this, below, we have undertaken a comparative analysis of XPS results, including our own research discussed in this review, in an effort to rectify any misleading analyses and offer perspectives and suggestions on XPS analysis. Regarding C 1s peak fitting, there is no doubt that the C-C peak at 284.8 eV is attributed to adventitious carbon from the ambient environment, commonly used as an internal calibration ref.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [22] investigated Cr 2 O 3 -coated NaCrO 2 and showed less deteriorated capacity fade at relatively high rates over bare NaCrO 2 . Similarly, Ikhe et al [23] have applied Cr 2 O 3 coating to Al-doped NaCrO 2, which also exhibited improved long-term cycle retention.…”
Section: Introductionmentioning
confidence: 99%
“…Under a current density of 10 C, after 1000 cycles, it still has a specific capacity of 100.4 mAh g À 1 with a retention rate of about 84.8 %. [28] On this basis, Ikhe et al [29] combined Cr 2 O 3 coating with Al doping and found that the specific capacity had almost no attenuation after 1000 cycles. All the above studies show that surface coating is a very useful strategy to improve the stability of materials.…”
Section: Introductionmentioning
confidence: 99%